ANALISIS KEMAMPUAN MENULIS HURUF MENGGUNAKAN BUKU BERGAMBAR BERSUARA PADA SISWA KELAS 1 SDN PERIUK 1 KOTA TANGERANG - Firyal Nada Salsaabila; Ezik Firman Syah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
First-grade elementary students still experience difficulties in writing letters, such as recognizing and distinguishing similar letter shapes, copying letters according to stroke direction, and using capital letters correctly. This problem is worsened by conventional and monotonous teaching methods that make students quickly feel bored. This study aims to analyze letter writing ability using sound picture books in first-grade students at SDN Periuk 1 Tangerang City.The research used a qualitative approach with a case study method. The research subjects were a first-grade teacher and nine students. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results show that sound picture books effectively help students recognize and write letters. This media combines visual and audio elements that help students associate letter shapes with their sounds. Teachers play an important role in guiding students to copy letters by providing examples and direct corrections. Students stated that this media makes learning easier and more enjoyable because they can see letter shapes while hearing their sounds. Sound picture books create an interactive and multisensory learning atmosphere, increasing student focus and enthusiasm. This media supports diverse visual and auditory learning styles, making it easier for students to understand and remember letters. This research provides practical contributions for teachers in selecting innovative learning media to improve letter writing skills of early-grade students in accordance with the Merdeka Belajar concept.